PENGARUH KUALITAS LAYANAN TERHADAP NIAT BERPERILAKU PASIEN RUMAH SAKIT UMUM DAERAH KABUPATEN PEKALONGAN - Siti Yunitarini (Jurnal Ekonomi Dan Bisnis, 2015)
This research was to know influence in quality service towards customer’s Behaviour Preference at General Hospital Residence of Pekalongan. It was also to measure a difference of influence slope in quality service on customer’s Behaviour Preference between above and bottom in tolerance zone base on that zone. And it was to measure significant difference in behaviour preference between customer who did not experienced problem of service and those who experienced this, and those that between solved problem of service and unsolved problem of serviceVariable   in   quality   of   service   referent   to   research   that   conducted   by Parasuraman, Zeithaml, and Berry (1985) including tangible, reliability, responsiveness, assurance, and emphaty variable. Behavioure Preferences variable referred to research that conducted by Zeithaml, Valerie A., et., al (1996) including loyalthy, switch, pay more, external response and internal response.Location of research held in General Hospital Residence of Pekalongan, with subject of research who become hospital service’s customer. To know influence in quality of service towards behaviour preference was used regression analysis and ANOVA. Result  of analysis  showed  that  was  positive influence significantly between quality of service and customer’s behaviour preference at General Hospital Residence of Pekalongan. There was significant difference between influence in quality of service and behaviour preference above and bottom zone of tolerance that based on tolerance zone. There is significant difference between customers behaviour preference ho did not experienced problem o service and those who experienced problem of service. And it also showed that there is significant difference between those who experience unsolved problem of service and those who experienced solved problem. It found that average score of highest behaviour preference is customer who did not experience problem of service, the next highest is customer’s who experience problem of service, but it can be solved, and the lowest for customer who experienced problem of service but solved.Based on result of research, all of hyphothesis (H1a, H1b, H2a, H2b, and H2c) were accepted. Qulity of service toward behaviour preference has positive influence, so that is was suggested that General Hospital Residence of Pekalongan to be aware in problem at quality of service Keywords :